Linguistic Borrowings and Terminology: the threads that intertwine French fashion and the English language - Oliveira, Ingrid (Entrepalavras, 2024)
This article, an excerpt from a doctoral research, aims to present and analyze twelve French-language women's fashion terms that have been borrowed from English. To this end, the theoretical assumptions of Cabré (1999), Finatto and Krieger (2004), and Krieger (2013) were followed within terminology studies. The data was selected by reading the fashion columns in five periodicals published between 1903-1930 (Le Figaro-Modes; Les Modes, Femina, Les modes de la femme de France, Le Petit écho de la mode). The results indicate the presence of two phases of borrowing, the first before the First World War (1914-1918), with a predominance of terms originating from England, and the second after the end of the conflict, with the presence of terms also coming from the United States. This fact proves the relationships of influence and prestige that exist between borrowings, languages and the groups that use them, and the importance of terminology studies in earlier phases of the language.